The goals and selection criteria of sports scholarships: mutual benefits perceived by South African schools' - Christopher Ekron; Brendon Knott; H. Thomas R. Persson; Mogammad Sharhidd Taliep (Frontiers in Sports and Active Living)
In South Africa (SA), the legacy of apartheid has resulted in significant disparities within the nation's education system. Elite schools may be public or private, offering a superior educational and sporting environment that is unaffordable for most of the population. However, it is common for these schools to offer sports scholarships to deserving recipients. The Social Exchange Theory (SET) can be used as a theoretical lens to understand the mutually beneficial nature of the relationship between the school and the sport scholarship recipient. While recipients gain educational and sporting opportunities, schools benefit from the athletic talent and boosts their competitive sporting edge and prestige status. Previous studies have considered the progression of the scholarship recipients. However, none have undertaken to explore a more nuanced understanding of the schools' perspective. This qualitative exploratory study, therefore, aimed to reveal the goals and selection criteria for sports scholarships among selected elite boys' high schools in SA. Eight in-depth interviews were conducted with senior staff members closely involved in the scholarship process from four elite boys' schools in the Western Cape, SA. The transcribed interviews were thematically analysed to understand the goals and selection criteria. The findings indicate that there are multifaceted goals for the schools. Beyond boosting the schools' sporting talent and achievement, the goals also included fostering diversity and nurturing holistic development among student-athletes. The selection criteria varied between schools, with criteria beyond sporting potential playing a key role, such as academic aptitude, character, consideration of the financial status of the applicant, and the financial impact on the school. The study highlights that sports scholarships in elite South African schools represent a complex interplay between opportunity and expectation, aligning with the SET lens. While scholarships serve as powerful tools for fostering individual growth and institutional excellence, their implementation requires careful consideration of social integration, financial sustainability and equitable access.